The impact of a short-term training program on workers’ sterile processing knowledge and practices in 12 Ethiopian hospitals: A mixed methods study - Fast, Olive M. (PLoS One, 2019)
BACKGROUND: The need for increased attention to surgical safety in low- and middle-income countries invited organizations worldwide to support improvements in surgical care. However, little is written about issues in instrument sterilization in low- and middle-income countries including Ethiopia. OBJECTIVE: The study aims to identify the impact of a sterile processing course, with a training-of-trainers component and workplace mentoring on surgical instrument cleaning and sterilization practices at 12 hospitals in Ethiopia. METHOD: A mixed-methods research design that incorporates both qualitative and quantitative research approaches to address issues in sterile processing was used for this study. The quantitative data (test results) were validated by qualitative data (hospital assessments, including observations and participant feedback). Twelve hospitals were involved in the training, including two university teaching hospitals from two regions of Ethiopia. In each of the two regions 30 sterile processing staff were invited to participate in a three-day course including theory and skills training; 12–15 of these individuals were invited to remain for a two-day training of trainers course. The collected quantitative data were analysed using a paired t-test by SPSS software, whereas comparative analysis was employed for the qualitative data. RESULTS: Process, structural, and knowledge changes were identified following program implementation. Knowledge test results indicated an increase of greater than 20% in participant sterile processing knowledge. Changes in process included improved flow of instruments from dirty to clean, greater attention to detail during the cleaning and decontamination steps, more focused inspection of instruments and careful packaging, as well as changes to how instruments were stored. Those trained to be trainers had taught over 250 additional staff. CONCLUSIONS: Increased attention to and knowledge in sterile processing practices and care of instruments with a short, one-week course provides evidence that a small amount of resources applied to a largely under-resourced area of healthcare can result in decreased risks to patients and staff. Providing education in sterile processing and ensuring staff have the ability to disseminate their learnings to other health care providers results in decreasing risks of hospital associated infections in patients.